STRATEGY FOR DEVELOPING ADVANCED BUSINESS FARMERS GROUPS USING THE HIERARCHY PROCESS (AHP) ANALYSIS METHOD IN NAGARI KOTO GADANG GUGUAK GUNUNG TALANG DISTRICT - Rahmi Hamidah; Faidil Tanjung; Mahdi Mahdi (LPPM Universitas Al Asyariah Mandar, 2024)
The corn commodity is one of the common crops cultivated in Nagari Koto Gadang Guguak, Solok Regency, so the cultivation of this corn plant has been cultivated for generations. Even though this corn plant is not yet optimal, it will continue to be developed over time. This research aims to determine the strategy for developing advanced business farmer groups in Solok Regency. This research identifies internal and external factors, formulates alternative strategies using SWOT analysis, then continues with arranging a hierarchy using AHP analysis. The results of internal and external analysis show that the Advanced Farmer Group has five strengths, two weaknesses, four opportunities and two threats. The land area for development is quite large and soil suitability is the most important subfactor of strength; poor financial records are the most important subfactor of weakness; the development of information technology is the most important subfactor in opportunities and pest and disease attacks are the most important subfactor in threats. The priority strategy that can be implemented in developing Advanced Business Farmer Groups based on the results of the AHP analysis is developing production by increasing the quality of both production results and production facilities and quantity.